Design and validation of a tunable inertial microfluidic system for the efficient enrichment of circulating tumor cells in blood. Issue 3 (29th April 2022) - Rodríguez‐Pena, Alejandro; Armendariz, Estibaliz; Oyarbide, Alvaro; Morales, Xabier; Ortiz‐Espinosa, Sergio; Ruiz‐Fernández de Córdoba, Borja; Cochonneau, Denis; Cornago, Iñaki; Heymann, Dominique; Argemi, Josepmaría; D'Avola, Delia; Sangro, Bruno; et al.
Abstract: The analysis of circulating tumor cells (CTCs) in blood is a powerful noninvasive alternative to conventional tumor biopsy. Inertial‐based separation is a promising high‐throughput, marker‐free sorting strategy for the enrichment and isolation of CTCs. Here, we present and validate a double spiral microfluidic device that efficiently isolates CTCs with a fine‐tunable cut‐off value of 9 μm and a separation range of 2 μm. We designed the device based on computer simulations that introduce a novel, customized inertial force term, and provide practical fabrication guidelines. We validated the device using calibration beads, which allowed us to refine the simulations and redesign the device. Then we validated the redesigned device using blood samples and a murine model of metastatic breast cancer. Finally, as a proof of principle, we tested the device using peripheral blood from a patient with hepatocellular carcinoma, isolating more than 17 CTCs/ml, with purity/removal values of 96.03% and 99.99% of white blood cell and red blood cells, respectively. These results confirm highly efficient CTC isolation with a stringent cut‐off value and better separation results than the state of the art.